2022
DOI: 10.53272/icrrd.v3i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Can Government Incentive on Remittance Encourages Remitters in Bangladesh? A Policy Study

Abstract: The government's recent two percent remittance incentive has attracted the attention of remitters and policymakers in Bangladesh. The purpose of this inward remittance incentive policy is to encourage remitters to send money in a legal manner. This will minimize illegal money transfers from overseas, and the government will be able to grow the reserve. The goal of this research is to investigate if the policy has had any recent impact on remitters and if there has been any change in money flow from overseas to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…However, Ahmed (2010) concluded that remittance inflow has a negative impact on economic growth. Afzal et al (2022) found that the remittance and reserve in Bangladesh are more closely correlated than the other South Asian countries such as Sri Lanka, Pakistan, and Bhutan. Naseem, Aslam, and Hassan (2012) concluded that there is a significant positive relationship between the rise of remittance inflow and the increase of foreign currency reserves in Bangladesh, Pakistan, and India.…”
Section: Literature Reviewmentioning
confidence: 95%
“…However, Ahmed (2010) concluded that remittance inflow has a negative impact on economic growth. Afzal et al (2022) found that the remittance and reserve in Bangladesh are more closely correlated than the other South Asian countries such as Sri Lanka, Pakistan, and Bhutan. Naseem, Aslam, and Hassan (2012) concluded that there is a significant positive relationship between the rise of remittance inflow and the increase of foreign currency reserves in Bangladesh, Pakistan, and India.…”
Section: Literature Reviewmentioning
confidence: 95%